Time-Lag and Accumulation Effects of Climate Change on Habitat Quality in the Chinese Loess Plateau - Le Chen; Wei Wei (Ecosystem Health and Sustainability)
Investigating the impacts of climate change on habitat quality is crucial for sustainable environmental management, ecological resilience, and ecosystem vitality. However, the complex dynamics—particularly time-lag and accumulation effects—remain insufficiently explored. This study addresses this gap by examining the interactions between habitat quality and key climatic factors—temperature, precipitation, and solar radiation—on the Loess Plateau from 2000 to 2020. Using the remote-sensing-based ecological index (RSEI) as a quantitative measure of habitat quality, the study systematically analyzed the time-lag and accumulation effects of these climatic factors on RSEI across both the entire vegetation growing period and monthly scales. The results showed the following: (a) There was a dominant increasing trend in RSEI across 92.32% of the plateau, with 66.3% showing significant increases and both “warming and humidifying” and “warming and drying” patterns observed. (b) Incorporating time-lag and accumulation effects enhanced the explanatory power of temperature, precipitation, and solar radiation for RSEI during the growing period by 15.71%, 12.76%, and 17.49%, respectively. (c) Precipitation’s time effects were primary drivers, with most regions showing 1- to 2-month lags. (d) Temperature and solar radiation impacts varied across biomes, with lags exceeding 2 months, leading to pronounced negative effects in the southern Loess Plateau. These findings highlight the complex time-lag and accumulation effects of climate change, influenced by climatic factors, topography, vegetation types, and temporal dynamics. The study underscores the vulnerability and complexity of the Loess Plateau’s ecosystems, emphasizing the need for strategic interventions to address climate challenges and providing valuable guidance for effective ecosystem management.